Ratio Legis Penambahan Modal Negara Kepada Lembaga Pembiayaan Ekspor Indonesia - Hidayat, Syarif (UI Scholars Hub, 2024)
Since its establishment under Law Number 2 of 2009 concerning The Indonesian Export Financing Institution (LPEI), the Indonesian Export Financing Institution has gained additional capital participation nine times between 2010 and 2021 by the passage of government regulations. The rules for extra capital in the legislation on its establishment only take the form of regulations in the event that the capital of the Indonesian Export Financing Institution is decreased by a particular amount, but the additional capital that has been carried out thus far is not meant to replace the capital deficiency. As a result, this research was undertaken to investigate the legal ratio of extra state capital to the Indonesian Export Financing Institution. Therefore, the purpose of this study was to investigate the legal ratio between the Indonesian Export Financing Institution and additional state capital. By examining secondary data in the form of statutory regulations and relevant literature, this study applies normative juridical methods. The study's findings present the legal ratio and the position of the Indonesian Export Financing Institution. The State Finance Law and State Treasury Law's authority can be used to track the government's addition of state capital participation to the Indonesian Export Financing Institution.